Comportamento ingestivo de cordeiros em sistemas de produção em pastagem de azevém - Ribeiro, Ticiany Maria Dias; Monteiro, Alda Lúcia Gomes; Piazzetta, Hugo von Linsingen; Carvalho, Paulo César de Faccio; Silva, Marina Gabriela Berchiol da [UNESP]; Silva, Cláudio José Araujo da; Natel, Andressa Satanna; Souza, Damaris Ferreira de; Meirelles, Paulo Roberto de Lima [UNESP] (My University, 2014)
The objective of this study was to evaluate the lambs behavior intake produced in grazing systems on ryegrass pasture (Lolium multiflorum) oversowned on Tifton-85 (Cynodon sp): 1- lambs weaned around 40 days of age in ryegrass pastures until slaughter; 2- lambs without weaning, in the same ryegrass pasture until slaughter; 3- lambs in ryegrass pasture without weaning, supplemented at creep feeding at 1% BW from 40 days of age to slaughter. The lambs ingestive behavior was observed through their grazing, rumination, sucking, creep feeding and other activities from August to September of 2005. The experimental design was completely randomized design with three repetitions and split-plot design on time, considering days and periods of days as subplots. Lambs grazing and suckling time were not affected (P>0.05). By systems of production; however, rumination time was reduced (p<0.05) and the other activities time (p<0.05) increased for creep feeding systems. The grazing time during the afternoon was higher (p<0.05) than during the morning, whereas the other activities were distributed homogeneously throughout the day. Meat lambs systems of production may change the ingestive behavior, but the grazing activity keep requiring the most of the time of the animals during the day.

Este estudio evaluó el comportamiento ingestivo de corderos engordados en sistemas de producción en raigrás (Lolium multiflorum) resembrado en Tifton 85 (Cynodon sp), como sigue: 1- corderos destetados a los 40 días de edad y en pasto hasta el sacrificio, 2- corderos en el potrero con sus madres hasta sacrificio sin el destete, 3- corderos suplementados durante la lactancia en creep feeding en la pastura de raigrás hasta sacrificio, sin el destete. Se realizaron evaluaciones de la conducta alimentaria de los corderos de Agosto a Septiembre de 2004, con la comprobación de las actividades de pastoreo, rumia, la lactancia materna, el acceso a la suplementación y otras actividades mediante el control temporal durante el día. El diseño experimental fue completamente casual con tres repeticiones y parcelas en el tiempo, teniendo en cuenta los días y los períodos como subparcelas. No se observó efecto (p> 0,05) de los sistemas sobre el tiempo de pastoreo y la lactancia, sin embargo, hubo una reducción en el tiempo de rumia (p <0,05), y el aumento de tiempo en otras actividades (p <0,05) para los corderos en la alimentación privada en creep feeding. El tiempo de pastoreo de la tarde fue superior (p <0,05) que en la mañana, y las actividades restantes se distribuyeron de manera uniforme durante todo el día. El sistema de producción de corderos puede cambiar los patrones de conducta de alimentación de los mismos, y el pastoreo es la actividad que exige más tiempo de los animales durante el día.

Este trabalho objetivou avaliar o comportamento ingestivo de cordeiros, terminados em sistemas de produção em pastagem de azevém (Lolium multiflorum) sobressemeado em Tifton 85 (Cynodon sp) nos tratamentos: 1- cordeiros desmamados precocemente, aos 40 dias de idade, e mantidos em pastagem de azevém até o abate; 2- cordeiros sem desmame, na mesma pastagem de azevém até o abate; 3- cordeiros sem desmame suplementados em creep feeding a partir de 40 dias de idade, na pastagem de azevém, até o abate. Foram realizadas avaliações do comportamento ingestivo dos cordeiros, de agosto a setembro de 2004, verificando as atividades de pastejo, ruminação, amamentação, acesso a creep feeding e outras atividades. O delineamento experimental foi inteiramente casualisado com 3 repetições e parcelas subdivididas no tempo, considerando os dias e períodos como subparcelas. Não houve efeito (p>0,05) dos tratamentos sobre o tempo de pastejo e amamentação, entretanto, houve redução no tempo de ruminação (p<0,05), e elevação do tempo em outras atividades (p<0,05) para cordeiros em creep feeding. O tempo de pastejo no período da tarde foi superior (p<0,05) ao da manhã, sendo que as demais atividades foram distribuídas homogeneamente ao longo do dia. O sistema de produção de cordeiros pode alterar os padrões de comportamento alimentar dos cordeiros, sendo que o pastejo é a atividade que demanda mais tempo dos animais durante o dia.
Ingestive behavior of lambs in production systems on italian ryegrass
Comportamiento ingestivo de corderos en sistemas de producción en pasto de raigrás
Keywords: Creep feeding; Grazing; Ruminating; Sheep; Suckling; Weaning; Lactancia; Suplementación; Destete; Ovejas; Pastoreo; Rumia; Amamentação; Creep feeding; Desmame; Ovinos; Pastejo; Ruminação